The kid in the red jacket - Park, Barbara (New York : Scholastic, 1987)
When ten-year-old Howard has to move with his family to a distant state, he is forced to live on a street named Chester Pewe, adjust to a new school, and get used to being shadowed by the little girl in a nearby house.
M
b
b
Keywords: Moving, Household -- Fiction; Humorous stories